Biological effect of Silver Nanoparticles synthesis by Leaves of Cymbopogon citratus on eggs and larvae of Cadra cautella (Walk.) (Lepidoptera: Pyralidae) - Sarah Ibrahim Mahmood (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
During storage and before consumption, grains often experience a decline in quality, nutritional content, and cleanliness due to pest attacks. Botanical insecticides are considered an alternative method to reduce dependence on harmful chemical pesticides. This study aimed to evaluate the effectiveness of three concentrations of silver nanoparticles (AgNPs) synthesized from the leaves of Cymbopogon citratus against Cadra cautella (Walk.) (Lepidoptera: Pyralidae) and their potential as biological control agents. The selection of C. cautella as the test organism was based on the limited number of studies examining this pest. The AgNPs used were synthesized through an eco-friendly method, and their optical and physical properties were analyzed using UV-Vis spectroscopy. The results demonstrated that AgNPs synthesized from C. citratus extract showed high effectiveness in controlling the eggs and second instar larvae of C. cautella. Egg mortality reached 80.3% at a concentration of 40 μg/ml after 24 hours of exposure, followed by 72.9% at 30 μg/ml, and 65.8% at 20 μg/ml. In contrast, the control group showed no egg mortality. Similarly, larval mortality rates were 74.9%, 65.8%, and 60.2% for concentrations of 40 μg/ml, 30 μg/ml, and 20 μg/ml, respectively. These findings indicate that higher concentrations of AgNPs lead to greater mortality in both eggs and larvae. This study highlights the potential of green-synthesized AgNPs from C. citratus leaves as an effective and eco-friendly biopesticide. Their significant impact on egg and larval mortality suggests that they can be developed as an alternative pest control strategy in stored grains, thereby reducing reliance on conventional chemical pesticides that are detrimental to human health and the environment. Further research is recommended to explore their long-term efficacy, safety, and integration into sustainable grain storage management.